Synchronous ovarian granulosa cell tumor and carcinoma endometrium due to excess estrogen secretion: a rare presentation - Asaithambi, Shubha Supriya; Swamy, Shruthi; V. Karpurmath, Shashidhar; Nandennavar, Manjunath; Angadi, Veerendra (International Journal of Research in Medical Sciences, 2024)
Granulosa cell tumor (GCT) is a low malignant potential ovarian tumor accounting for 70% of all sex cord stromal tumor. It is an estrogen secreting tumor, hence diagnosed in early stages, associated with 20-30% concomitant lesion in endometrium including 5% of invasive adenocarcinoma. Through this case report we present the synchronous occurrence of ovarian and endometrial malignancy of a 52-year-old female, P3L2A0 who presented with irregular menstrual bleeding since 2 months along with literature review. Imaging showed endometrial lesion with synchronous left ovarian lesion with a normal CA-125. Underwent total abdominal hysterectomy with bilateral salphingo-oophorectomy and post op histopathology showed FIGO stage IC GCT of left ovary and Endometrioid carcinoma of endometrium, grade1, FIGO stage IA, low risk with P-53 negative by IHC. In view of ovarian tumor FIGO stage IC GCT, she received adjuvant chemotherapy. Hence, presence of synchronous endometrial lesion with suspicious ovarian mass at presentation should suspect the diagnosis of estrogen secreting GCT with endometrial lesion.